Evaluation of Reliability and Validity of the Persian Version of Fatigue Severity Scale (FSS) among Persons with Multiple Sclerosis - A'zam Shahvarughi-Farahani; Mojtaba A'zimian; Mandana Fallah-Pour; Masoud Karimlou (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: The aim of this study was to evaluate different aspects of validity and reliability of the Persian-version of Fatigue Severity Scale (FSS-P) among people with Multiple Sclerosis. Materials & Methods: A sample of 50 people with Multiple Sclerosis and 30 healthy adults were included in this study. The participants were recruited from Sina clinic in Tehran between 2001 to 2007. The Fatigue Severity Scale (FSS) includes nine items developed to measure disabling fatigue and a Visual Analog Scale (VAS) to measure overall fatigue. All participants were asked to complete FSS and Short-form 36 Health Survey (SF-36) questionnaires. Test-retest reliability and Internal Consistency were assessed, using Intraclass Correlation Coefficient (ICC) and Cronbach's alpha, respectively. Dimensionality was assessed, using item-scale correlation after correction for overlap and convergent validity, using a priori hypothesized correlations with the SF-36. Results: All the participants found the FSS-P to be clear and unambiguous in pilot testing. The ICC was reported 0.93 for the total score and 0.88 for VAS, The Cronbach's alpha was reported 0.96. The total score and the VAS were significantly correlated with the SF-36 vitality subscale (r=-0.69 and r=-0.73 respectively). Correlations with other SF-36 subscales were at moderate level (r=-0.43 to r=-0.65, all P<0.001). Conclusion: Since this is the first study to translate and scale equivalent to "fatigue severity scale" in Farsi in Iran, the main features of the scale and reliability of Persian version of "fatigue severity scale" was determined and assess the validity of the study in terms of facilities and access to the sample and a preliminary report in order to design more and more research was in order next. The results of the study revealed that the FSS-P is an appropriate psychometric instrument to assess the people with Multiple Sclerosis.